Profile Overview of Endometriosis Sufferers at Cengkareng Hospital in 2021 - Kathleen Juanita Gunawan Soenario; Frizar Irmansyah; Alisa Febriyanti (Jurnal MedScientiae, 2023)
Endometriosis is a benign gynecological disease characterized by the presence of part of the endometrial tissue outside the uterine cavity. Symptoms that occur in endometriosis can include menstrual pain, painful intercourse, chronic pelvic pain and infertility. The purpose of this study was to see the Profile of Endometriosis Sufferers at Cengkareng Hospital, Jakarta. The research method is descriptive method with a cross sectional approach, where data collection is carried out only once using medical record data. The study was conducted on patients at Cengkareng Hospital, by collecting data for 1 month. Data processing using SPSS version 25. The results of this study showed that 72 respondents found that the incidence of endometriosis at Cengkareng Hospital was in 2021. More endometriosis patients occurred with supporting examinations carried out by ultrasound, Laparotomy and Anatomical Pathology (51.4%), symptoms of dysmenorrhea (56 .9%), age 36-45 years (55.6%), ideal BMI 18.5 – 25.9 (56.9%), nullipara (98.6%), married status (79.2%). The conclusion is that most endometriosis patients are aged 36-45 years, with married status, nullipara, symptoms of dysmenorrhea, ideal BMI, and supporting ultrasound examinations, Laparotomy and Anatomical Pathology.